2011
DOI: 10.1002/pca.1318
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Eleven Phenolic Compounds Including Novel p‐Coumaroyl Derivatives in Lettuce (Lactuca sativa L.) by Ultra‐high‐performance Liquid Chromatography with Photodiode Array and Mass Spectrometry Detection

Abstract: The main intact phenolic compounds, including four novel p-coumaroyl esters, were simultaneously quantified in lettuce with optimal performances and a reduced total time of analysis. These findings make headway in the understanding of the lettuce phytochemicals with potential nutritional relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
46
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 30 publications
16
46
1
Order By: Relevance
“…Undifferentiated cultures of the both plant species were poor sources of hydroxycinnamates. Aerial parts of Lactuca sativa L. intact plants accumulated DCTA as major caffeic acid derivative and only minor amounts of 3,5-DCQA (Degl'Innocenti et al 2008;Ribas-Agustí et al 2011). In the roots of L. sativa and L. virosa plants cultivated in our garden, contents of DCTA were similar to those of 3,5-DCQA (Table 1).…”
Section: Resultsmentioning
confidence: 51%
“…Undifferentiated cultures of the both plant species were poor sources of hydroxycinnamates. Aerial parts of Lactuca sativa L. intact plants accumulated DCTA as major caffeic acid derivative and only minor amounts of 3,5-DCQA (Degl'Innocenti et al 2008;Ribas-Agustí et al 2011). In the roots of L. sativa and L. virosa plants cultivated in our garden, contents of DCTA were similar to those of 3,5-DCQA (Table 1).…”
Section: Resultsmentioning
confidence: 51%
“…The composition of the essential oil of lettuce differs, depending on where it is grown as well as the environmental conditions. The differences in chemical composition, which can affect the biological activities and pharmaceutical applications, are probably due to the differences in the climatic and geographical conditions (temperature, rainfall, altitude, hours of sunshine, etc) [5,7,9,11,13,[15][16][17][18] . Only a few chemical constituents were present in both essential oils.…”
Section: Discussionmentioning
confidence: 99%
“…A HPLC method (INA-Institute for Nutraceutical Advancement method 106.000) from NSF (National Science Foundation) International (Ann Arbor, MI, USA) is accessible as well. Clear chicoric acid mass spectra examples can be found in Shiga et al (2009) and Mulinacci et al (2001); mother and fragmented masses have been reported in numerous papers with various MS settings, so one of these references can be used for comparison with a comparable analysis (Mulinacci et al, 2001; Baur et al, 2004; Lee and Scagel, 2009; Shiga et al, 2009; Pellati et al, 2011; Ribas-Agusti et al, 2011; Carazzone et al, 2013). …”
Section: Identification Synthesis and Biosynthesis Chicoric Acidmentioning
confidence: 99%
“…So, it is not surprising that among three popular and widespread Echinacea dietary supplements, preparations of E. purpurea contained higher levels of chicoric acid than either E. pallida or E. augustifolia (Perry et al, 2001; Binns et al, 2002; Pellati et al, 2005). Chicoric acid can also vary greatly between cultivars; Kwee and Niemeyer (2011) examined 15 basil cultivars and reported a chicoric acid range from 3 to 278 mg 100 g −1 dry weight (93 fold difference; and Ribas-Agusti et al (2011) recorded chicoric acid concentrations from 23 to 1388 mg 100 g −1 fresh weight when they evaluated 13 cultivars of romaine lettuce.…”
Section: Plant Kingdom and Within Plant Distributionmentioning
confidence: 99%